Conceptual Frameworks in the Field of IT Management: Preliminary Study - Anita ROMANOVA; Matej CERNY (Communications of International Proceedings, 2021)
The IT management area is one of the most discussed areas, which was triggered by changes in IT development, their importance, and the view of IT. A look at IT is no longer just a view at the technologies themselves, but at their importance in business activities and IT management in the business context. The aim of this scientific paper is to explore conceptual frameworks used in companies in the area of information technologies selected based on foreign and domestic literature. Selected conceptual frameworks are focused on covering all areas in IT from the IT governance, trough IT service management and security to financial assessment, quality and process control. In the second part we have focused on the analysis of the results of the preliminary questionnaire survey. We have analyzed how the companies operating in Slovak republic use the conceptional frameworks and how is this use affected by various factors.
Keywords: Information Technology; Conceptual frameworks; ITIL; ISO/IEC.